Improving a course module by introducing it differently and including a dialog based summative feedback - analysis of students’ perception of changes made - Skive, Bolette (Improving University Science Teaching and Learning, 2023)
The project focuses on a two-week course in meat inspection, which is a mandatory part of the veterinary master curriculum. In short the course teaches how to evaluate the safety of meat meant for human consumption at abattoirs theoretically and practically, and how to do inspection and auditing of food safety management systems in food producing companies, in this context at the abattoir and an attached retail butchers shop.